The Importance of Historical and National Colors in Translation - Abdikhamidova Sevinch Obidjon kizi (Euro Asian Journal Publishing, 2024)
In this article the pivotal role of incorporating national and historical elements in the translation process is explored. It delves into how these concepts are metaphorically represented as “colors” by analyzing their accurate and contextually rich meanings
Keywords: language and culture; translation; national elements; authenticity